2007
DOI: 10.1002/mop.22506
|View full text |Cite
|
Sign up to set email alerts
|

Building a resonant cavity for the measurement of microwave dielectric permittivity of high loss materials

Abstract: The design of a cavity resonator implies to solve the Maxwell equations inside that cavity, respecting the boundary conditions. As a consequence, the resonance frequencies appear as conditions in the solutions of the differential equation involved. The measurement of the complex permittivity, ϵ* = ϵ′‐iϵ″, can be made using the small perturbation theory. In this method, the resonance frequency and the quality factor of the cavity, with and without a sample, can be used to calculate the complex dielectric permit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 14 publications
0
57
0
3
Order By: Relevance
“…To measure the complex permittivity of the material, e* ¼ e 0 Àie 00 , a cavity perturbation method was used [7], in a rectangular cavity, operating in the TE 1,0,11 mode, at about 5 GHz. In the centre of the cavity, where the electrical field is maximal, the sample is inserted, provoking the perturbation of the field.…”
Section: Methodsmentioning
confidence: 99%
“…To measure the complex permittivity of the material, e* ¼ e 0 Àie 00 , a cavity perturbation method was used [7], in a rectangular cavity, operating in the TE 1,0,11 mode, at about 5 GHz. In the centre of the cavity, where the electrical field is maximal, the sample is inserted, provoking the perturbation of the field.…”
Section: Methodsmentioning
confidence: 99%
“…According to the small perturbation theory, 16 a linear relationship exists between the frequency shift ⌬f caused by the insertion of a sample in the cavity and the real part of the complex permittivity of the material Ј. The same behavior is observed in the change in the inverse of the quality factor of the cavity, ⌬͑1 / Q͒, related to the imaginary part, Љ.…”
mentioning
confidence: 87%
“…16 In the center of the cavity, where the electrical field is maximal, the sample is inserted, provoking the perturbation of the field. As a consequence, the transmission of the cavity changes.…”
mentioning
confidence: 99%
“…Resonant methods have much better accuracy and sensitivity than nonresonant methods [1,13,14]. They are generally applied to characterization of low-loss materials.…”
Section: Introductionmentioning
confidence: 99%
“…They are generally applied to characterization of low-loss materials. In a recent study, it has been shown that they are also applicable to high-loss materials provided that very small samples are prepared or higher volume cavities are constructed [13]. Though, a meticulous sample preparation is needed before measurements.…”
Section: Introductionmentioning
confidence: 99%